2009
DOI: 10.1093/eurheartj/ehp184
|View full text |Cite
|
Sign up to set email alerts
|

Relation of functional and morphological changes in mitochondria to myocardial contractile and relaxation reserves in asymptomatic to mildly symptomatic patients with hypertrophic cardiomyopathy

Abstract: Mitochondria showed functional impairment and morphological disorganization in the left ventricle of HCM patients without baseline systolic dysfunction. These mitochondrial changes were associated with impaired myocardial contractile and relaxation reserves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 34 publications
2
44
0
4
Order By: Relevance
“…We previously revealed that Ca 2+ -handling 6) and mitochondrial 7) mRNA may contribute to impaired myocardial contractile reserve in HCM patients. The results of this study are consistent with those of our previous studies, 6,7) suggesting that the changes in troponins, Ca 2+ -handling, and mitochondrial function may represent ongoing myocardial damage even in clinically and hemodynamically stable HCM patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously revealed that Ca 2+ -handling 6) and mitochondrial 7) mRNA may contribute to impaired myocardial contractile reserve in HCM patients. The results of this study are consistent with those of our previous studies, 6,7) suggesting that the changes in troponins, Ca 2+ -handling, and mitochondrial function may represent ongoing myocardial damage even in clinically and hemodynamically stable HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of primers and TaqMan probes specific for human sarcoendoplasmic reticulum Ca 2+ -ATPase 2 (SERCA2), phospholamban (PLB), troponin T2 (TNNT2), troponin I3 (TNNI3), cytochrome c oxidase subunit 5B (COX5B), nicotinamideadenine dinucleotide (NADH) dehydrogenase (ubiquinone) flavoprotein3 (NDUFV3), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were described previously. 7) All determinations were performed in triplicate. The abundance of each target mRNA was normalized by the corresponding amount of GAP-DH mRNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12, 13 The MoF pattern was defined as a progressive increase in LV dP/dtmax with increases in the pacing rate, whereas the BiF pattern was defined as an initially positive slope followed by a negative slope, with a decrease in LV dP/dtmax >5% from the highest value to the value at the maximum pacing rate. 12, 13 Representative traces for the patients with MoF and BiF patterns are shown in Figure 1A.…”
Section: Ffr Patterns and Patient Classificationmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that either a flat or a negative FFR pattern is indicative of limited contractile reserve in HCM. 12, 13 However, it remains unclear whether changes in FFR affect clinical outcomes or if a BiF is associated with a poor prognosis in the setting of HCM. Therefore, we investigated the promising role of the FFR as a predictor of cardiac events in the setting of HCM during the disease's clinically asymptomatic stages.…”
mentioning
confidence: 99%